Variable Temporal Cerebral Blood Flow Response to Acetazolamide in Moyamoya Patients Measured Using Arterial Spin Labeling - Fahlström, Markus; Wikström, Johan; Borota, Ljubisa; Enblad, Per; Lewén, Anders (Frontiers in Neurology, 2021)
Cerebrovascular reserve capacity (CVR), an important predictor of ischaemic events and a prognostic factor for patients with moyamoya disease (MMD), can be assessed by measuring cerebral blood flow (CBF) before and after administration of acetazolamide (ACZ). Often a single CBF measurement is performed between 5 to 20 min after ACZ injection. Assessment of the temporal response of the vasodilation secondary to ACZ administration using several repeated CBF measurements has not been studied extensively. Furthermore, the high standard deviations of the group-averaged CVRs reported in the current literature indicate a patient-specific dispersion of CVR values over a wide range. The aim of this study was to assess the temporal response of the CBF and derived CVR during ACZ challenge using arterial spin labelling (ASL) in patients with MMD. Eleven patients with MMD were included before or after revascularisation surgery. CBF maps were acquired using pseudo-continuous ASL before and 5, 15 and 25 min after an intravenous ACZ injection. A vascular territory template was spatially normalised to patient-specific space, including the bilateral anterior, middle and posterior cerebral arteries. CBF increased significantly post-ACZ injection in all vascular territories and at all time points. Group-averaged CBF and CVR values remained constant throughout the ACZ challenge in most patients. Maximum increase in CBF occurred most frequently at 5 min post-ACZ injection. However, peaks at 15 min or 25 min were also present in some patients. In 68% of the affected vascular territories, the maximum increase in CBF did not occur at 15 min. In individual cases, difference in CVR between different time points was between 1 to 30 percentage points (mean difference 8 percentage points). In conclusion, there is a substantial variation in CVR between different time points after ACZ challenge in patients with MMD. Thus, there is a risk that use of a single post-ACZ measurement time point overestimates disease progression, which could have wide implications for decision-making regarding revascularization surgery and the interpretation of the outcome thereof. Further studies with larger sample sizes using multiple CBF measurements post-ACZ injection in patients with MMD are encouraged.